Vitamin D level among patients with unexplained musculoskeletal symptoms - Md. Abdur Razzaque; Iftekhar Hussain Bandhan; Rijwan Bhuiyan; Mohammad Ziaul Haider; Mirza Nurul Karim; Minhaj Rahim Choudhury (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Background: Unexplained musculoskeletal (MSK) symptoms sometimes pose diagnostic and management challenges and can lead to prolonged suffering and disability. Hypovitaminosis D could be a reason for such symptoms. This study aimed to determine the vitamin D level among patients with unexplained MSK symptoms.